INDONESIA-MALAYSIA MARITIME BOUNDARIES DELIMITATION: A RETROSPECTIVE - Eddy Pratomo (International Law Department, Faculty of Law Universitas Padjadjaran, 2019)
Abstract“Good fences make good neighbors.” But how long should one build those fences with its neighbor? Boundary delimitation has always been an eye-catching issue in international law and international relations. Sometimes it can take up for many years. States tend to be very cautious in delimiting its boundary because once it is agreed, it cannot be changed anymore. Indonesia-Malaysia maritime boundary is not an exception. These two relatively young nations have negotiated their maritime boundaries since the 1960's. More than fifty years later, maritime boundary segments still remain to be settled. But where does it stand now? This article will highlight a number of important issues of the Indonesian-Malaysian maritime boundaries delimitation, the latest development, and the way forward on where these two nations will proceed. Keywords: Archipelagic Baseline, Boundary Agreement, Continental Shelf, Exclusive Economic Zone, Maritime Delimitation Abstrak“Good fences make good neighbor”. Tetapi berapa lama waktu yang diperlukan untuk menegosiasikan pagar tersebut? Delimitasi batas negara selalu menjadi isu hangat dalam hukum dan hubungan internasional. Proses ini dapat memakan waktu bertahun-tahun. Negara-negara cenderung untuk sangat berhati-hati dalam menegosiasikan batas, karena setelah perbatasan tersebut disepakati, maka batas tersebut tidak dapat diubah.Batas maritim Indonesia dan Malaysia tidak terkecuali. Kedua negara yang relatif masih muda ini telah menegosiasikan batas maritimnya sejak tahun 1960an. Lebih dari lima puluh tahun kemudian, segmen-segmen batas maritim antar kedua negara juga belum selesai dirundingkan. Setelah sekian lama berunding, bagaimana perkembangan proses penetapan batas maritim kedua negara? Artikel ini akan mengedepankan isu-isu penting terkait dengan delimitasi batas maritim Indonesia-Malaysia, perkembangan terakhir, dan langkah kedepan yang akan ditempuh oleh kedua negara. Kata kunci: Delimitasi Batas Maritim , Garis Pangkal Kepulauan, Landas Kontinen, Perjanjian Perbatasan, Zona Ekonomi Eksklusif,